The Role of Recycling Strategies in Mitigating the Impact of Waste Externalities on Environmental Accounting Implementation - Saputra, Komang Adi Kurniawan; Laksmi, Putu Ayu Sita; Noordin, Noorliza MD. (Journal of Environmental Accounting and Management, 2026)
This study aims to analyze the impact of waste externalities on the implementation of environmental accounting and explore the mediating role of recycling strategies in this relationship. The research seeks to provide insights into how recycling can bridge the gap between waste management challenges and environmental accountability. A correlational research design was employed, with data collected through surveys from 150 companies in Bali's tourism and manufacturing sectors. The study used regression analysis and the Sobel test to examine the relationships between waste externalities, recycling strategies, and environmental accounting implementation. The findings revealed a significant negative correlation between waste externalities and environmental accounting implementation, indicating that higher externality challenges reduce accounting practices. Companies adopting recycling strategies demonstrated better environmental accounting practices, suggesting that recycling enhances awareness and accountability. The study concludes that while waste externalities hinder environmental accounting, recycling strategies effectively mitigate these challenges by promoting sustainable practices. Businesses are encouraged to integrate recycling into their operations to improve environmental accountability. The findings also underscore the need for government policies to support sustainable waste management and stakeholder engagement. Future research should explore additional factors influencing these relationships across different regions and industries.